Large Ovarian Microcystic Stromal Tumour: A Report of Rare and Distinctive Pathological Entity - Rhea Sharon Susihar; Kalaivani Amitkumar; Meethu Rappai (Journal of Clinical and Diagnostic Research)
Microcystic Stromal Tumours (MCSTs) of the ovary are an exceedingly rare and distinct subtype of ovarian stromal neoplasms, characterised by their unique histopathological features. They were first identified in 2019 as a distinct entity. Hereby, the authors present a case report that focuses on a 48-year-old Indian female patient who presented with complaints of lower abdominal heaviness for the past year. Contrast-enhanced Computed Tomography (CECT) of the abdomen revealed a 29.7×24.4×15.3 cm hypodense lesion extending from the pelvis to the epigastric region, with multiple thick septations, a mural nodule/solid component, and moderate enhancement of the cyst wall. Preoperative blood values for CA 19-9, Carcinoembryonic Antigen (CEA), and CA-125 were 25.3 U/mL, 1.5 ng/mL, and 28.8 U/mL, respectively. Staging laparotomy combined with bilateral salpingo-oophorectomy and total hysterectomy was performed. Microscopic evaluation showed solid areas of spindle-shaped tumour cells intermixed with microcysts, separated by hyalinised fibrous stroma. The tumour cells displayed positive staining for vimentin and CD10 on Immunohistochemical (IHC) examination, but negative staining for calretinin and inhibin. Considering the histopathological features and immunohistochemical marker study, a diagnosis of microcystic stromal tumour was established. To date, approximately 50 cases have been documented worldwide, with only one case reported by an Indian author. This report highlights the importance of considering MCST in the differential diagnosis of ovarian masses and emphasises the role of histopathological and immunohistochemical evaluation in achieving an accurate diagnosis.